Evaluasi Pelaksanaan Kurikulum Merdeka di SMK Negeri 1 Pariaman - Ramadhani, Atsil Nabila; Haq, Syaiful; Silalahi, Juniman; Jufri, Windry Novalia (TSAQOFAH, 2025)
The Merdeka Curriculum is designed to improve the quality of education through a student-centered learning approach; however, in its implementation at SMK Negeri 1 Pariaman, several challenges were found that hindered the achievement of these objectives. This study aims to evaluate the implementation of the Merdeka Curriculum at SMK Negeri 1 Pariaman using the CIPP evaluation model (Context, Input, Process, and Product). The method used is descriptive research with a mixed method approach, involving 52 respondents consisting of the school principal, the vice principal for curriculum, DPIB teachers, and XI DPIB students. Data collection techniques were carried out through questionnaires, interviews, observations, and documentation. The results indicate that in the category of "Fairly Good," the context aspect shows that the school has understood the goals and urgency of the Merdeka Curriculum but is not yet fully prepared in terms of resources. In the input aspect, there is a limitation in teachers' understanding of teaching materials and the concept of flexible learning. The learning process is still predominantly teacher-centered, which contradicts the principles of the Merdeka Curriculum that emphasize student activity, while in the product aspect, the learning outcomes do not fully reflect the targeted learning achievements. This study concludes that the implementation of the Merdeka Curriculum at SMK Negeri 1 Pariaman still requires improvements in terms of teacher readiness, supporting facilities, and understanding of the curriculum's characteristics in order to achieve optimal results.